Detection and application of neurochemical profile by multiple regional 1H‐MRS in Parkinson's disease. Issue 9 (13th August 2017) - Guan, Jitian; Rong, Yu; Wen, Ye; Wu, Huanze; Qin, Hong; Zhang, Qingying; Chen, Wei
Abstract: Introduction: The accurate diagnosis and monitoring of idiopathic Parkinson disease (PD), a progressive neurodegenerative disorder, has not been fully developed. This study sought to identify a neurochemical profile in multiple regions of the PD brain and healthy controls by proton magnetic resonance spectroscopy ( 1 H‐MRS). We aimed to track changes of the brain neurochemical, quantify neuronal loss, and further determine the diagnostic value of 1 H‐MRS. Methods: PD patients and healthy controls recruited from Second Affiliated Hospital of Shantou University Medical College, Shantou, southern China, underwent 1 H‐MRS. Chemical information was obtained for ratios of N‐acetylaspartate to creatine (NAA/Cr), NAA to choline (NAA/Cho), and Cho to Cr for substantia nigra, globus pallidus, prefrontal lobe, hippocampus, cuneus gyrus, and dorsal thalamus regions. Results: Compared to the 20 healthy controls (12 male, age 58.75 ± 5.03 years), the 42 patients (21 male, age 61.60 ± 6.40 years) showed lower NAA/Cr and NAA/Cho ratios in substantia nigra, globus pallidus, prefrontal lobe, hippocampus, cuneus gyrus and dorsal thalamus regions ( p < .01); NAA/Cr and NAA/Cho ratios were reduced for both patients with unilateral and mild/no cognitive impairment ( p < .01); Unified Parkinson's Disease Rating Scale score was inversely correlated with NAA/Cr ratios in the substantia nigra ( r = −.32; p = .042). Conclusion: NAA/Cr and NAA/Cho ratios may be useful metabolic biomarkers for early diagnosis of PD. Multi‐voxel 1 H‐MRS can provide information on brain neurochemistry and may be a promising technique for diagnosis of and monitoring neuronal loss in PD. Abstract : Our study aimed to use a multi‐voxel 1H‐MR spectroscopic approach to track changes of the brain neurochemical, quantify neuronal loss, and further determine the diagnostic value of 1H‐MRS.